(untitled) (International Journal of Physiotherapy, 2016)
Introduction: Among musculoskeletal disorders knee Osteoarthritis (OA) is exceedingly prevailing articular disorder affecting people and it is a major cause of disability and socioeconomic burden. It is more common in women than men. Entities with knee OA must often undergo a variety of problems, such as pain and tenderness in joints, movement limitation, crepitus on movement, swelling, recurrent effusion, and local inflammation which ultimately leads to limitation in physical function, like lack of ability to perform Activities of Daily Living (ADL) or Instrumental Activities of Daily Living (IADL). For reducing knee pain in osteoarthritis several conventional treatment methods are used world widely but most extensively used in our country are pharmacologic and physical therapy. The objective of the study is to find out the effectiveness of Manual therapy verses Exercise therapy for the management of knee osteoarthritis. Methods: Sixty patients including both male and female with mean age (51years) and SD of (5.1) were enrolled in the study and divided randomly in to two groups. Those who were assigned as group A had received Manual therapy and those who were assigned as group B had received Exercise therapy. Participants had received three treatment sessions of 30 min per week for consecutive 4 weeks. OUTCOME MEASURE: WOMAC index score for pain, stiffness and physical function was used to evaluate the baseline score and treatment effects after 12 therapy sessions. Results: Study showed significant improvement in both groups before and after the treatment but in comparison manual therapy group showed significant results with respect to pain subscale (p=0.003) and physical function subscale (p=0.004). Conclusion: Significant difference found between manual therapy and exercise therapy treatment approaches in treating knee osteoarthritis. Findings of this study revealed the fact that short term treatment sessions of manual therapy were superior to exercise therapy in terms of alleviating pain, stiffness and functional limitation.